Abnormal neurodevelopment outcome in case of neonatal hyperekplexia secondary to missense mutation in GLRB gene. Issue 12 (15th December 2020) - Gupta, Naveen Parkash; Verma, Vinita; Chopra, Saurabh; Choudhury, Vivek
Abstract : Hyperekplexia is an exaggerated startle to external stimuli associated with a generalised increase in tone seen in neonates with both sporadic and genetic predisposition. This is an uncommon neurological entity that is misdiagnosed as seizure. A 28-days-old infant was admitted to us with characteristic intermittent generalised tonic spasm being treated as a seizure disorder. The infant had characteristic stiffening episode, exaggerated startle and non-habituation on tapping the nose. Hyperekplexia was suspected and confirmed by genetic testing (mutation in the β subunit of glycine was found). Initial improvement was seen with the use of clonazepam, which was not sustained. At the age of 4.5 years, the child is still having neurobehavioural issues like hyperactivity and sensory hyper-responsiveness. Usually, hyperekplexia is benign in nature. We report a case of hyperekplexia with non-sense mutation in the β subunit of GlyR gene having abnormal neurodevelopmental findings at 4.5 years.